Analysis of Islamic Religious Education Curriculum at Integrated Islamic Junior High School (SMP IT) Bina Mulya Ngamprah Bandung Barat - Hidayat, Nur; Suhana, Suhana; Ruswandi, Uus; Arifin, Bambang Samsul (STAI AL-FALAH CICALENGKA, 2021)
The purpose of this study was to determine the objectives of the Islamic Religious Education curriculum, the contents of the Islamic Religious Education curriculum, the Islamic Religious Education curriculum materials, and to find out the model for the implementation of the Islamic Religious Education curriculum at SMP IT Bina Mulya Ngamprah West Bandung. This type of research was qualitative research. While the data collection techniques in the form of observation, interviews, and documentation studies. The results of this study indicate that the goal of the PAI curriculum at SMP IT Bina Mulya is to foster faith through giving examples, fertilizing, and developing knowledge, appreciation, practice, habituation, and the experience of students about the religion of Islam. While the contents of the Islamic Religious Education curriculum structure at SMP IT Bina Mulya is an integration of the national PAI curriculum and the uniqueness of the Integrated Islamic School, i.e. the serial PAI module material (Aqidah, Tafsir, Hadith, Fiqh, Siroh, Adab and Tsaqofah). Quantum Learning, modeling systems, riyadhah systems, Outdoor Natural Learning, various learning strategies, and varied learning methods. Keywords: Model, Curriculum, Islamic Religious Education, Integrated Islamic School Abstrak Tujuan penelitian ini adalah untuk mengetahui tujuan kurikulum Pendidikan Agama Islam, isi kurikulum Pendidikan Agama Islam, materi kurikulum Pendidikan Agama Islam, serta mengetahui model penyelenggaraan kurikulum Pendidikan Agama Islam di SMP IT Bina Mulya Ngamprah Bandung Barat. Jenis penelitian ini adalah penelitian kualitatif. Sedangkan teknik pengumpulan data berupa observasi, wawancara, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa tujuan kurikulum PAI di SMP IT Bina Mulya adalah menumbuh kembangkan keimanan melalui pemberian ketauladanan, pemupukan, dan pengembangan pengetahuan, penghayatan, pengamalan, pembiasaan, serta pengalaman peserta didik tentang agama Islam. Sedangkan Isi struktur kurikulum Pendidikan Agama Islam di SMP IT Bina Mulya merupakan integrasi kurikukulum PAI nasional dan Kekhasan Sekolah Islam Terpadu yaitu dengan serial materi modul PAI ((Aqidah, Tafsir, Hadits, Fiqih, Siroh, Adab dan Tsaqofah). Sementara model pembelajaran menggunakan sistem pembelajaran Quantum Learning, sistem modeling, sistem riyadhah, Pembelajaran OutdoorAlam, Strategi Pembelajaran yang beragam, serta metode pembelajaran yang bervariasi. Kata Kunci:: Model, Kurikulum, Pendidikan Agama Islam, Sekolah Islam Terpadu.